IMPLEMENTASI PENDIDIKAN KEPRAMUKAAN DALAM MENANAMKAN KARAKTER PEDULI SOSIAL DAN RELEVANSINYA DENGAN PENDIDIKAN AGAMA ISLAM SISWA KELAS XII MADRASAH ALIYAH NU HASYIM ASY’ARI 2 KUDUS - Niswatul Arifah; Mukh. Nursikhin; Ulfa Nurul Masruroh (Universitas Islam Madura, 2023)
Scouting education is a vehicle for the formation of student morale which is carried out in Gugus Depan which is based in schools as an effort to develop student character through the learning process in the form of extracurricular activities. Implementation of scouting education based on Tri Satya and Dhasadarma which is relevant to akhlakul karimah education, with indicators of socially caring character (caring, respect, respect and cooperation). The research method used is qualitative naturalistic through active participation in scouting activities. The results of the study show that the activities that have succeeded in providing experience to students are related to the character of social care through scouting activities. Community activities such as the character of social care: 1) Planned activities (monthly and yearly), 2) Character of social care, such as the commemoration of Islamic holidays for social service and environmental service, 3) Supporting factors: careful planning, adequate facilities, and support from all institutional component. While the obstacles are: the low level of enthusiasm of the members, the short time allocation, and the lack of parental support. The implication of this research is that the character that is instilled in scouting activities is a social concern so it becomes important to be used as an additional competency for the implementation of formal education activities in educational institutions and schools.